2010
DOI: 10.1021/nn9012065
|View full text |Cite
|
Sign up to set email alerts
|

Fast Li-Ion Insertion into Nanosized LiMn2O4 without Domain Boundaries

Abstract: The effect of crystallite size on Li-ion insertion in electrode materials is of great interest recently because of the need for nanoelectrodes in higher-power Li-ion rechargeable batteries. We present a systematic study of the effect of size on the electrochemical properties of LiMn(2)O(4). Accurate size control of nanocrystalline LiMn(2)O(4), which is realized by a hydrothermal method, significantly alters the phase diagram as well as Li-ion insertion voltage. Nanocrystalline LiMn(2)O(4) with extremely small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
225
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(240 citation statements)
references
References 53 publications
12
225
1
2
Order By: Relevance
“…3a,b) and 2.3 V versus Na/Na þ (n-doping process, Fig. 3c,d) after achieving each quasi-equilibrium state 46 in order to probe the physical and/or chemical phenomena at the interface between the BPOE and the electrolyte solution. A frequency range of 10 mHz-10 kHz with an amplitude of 10 mV was applied in all EIS measurements.…”
Section: Resultsmentioning
confidence: 99%
“…3a,b) and 2.3 V versus Na/Na þ (n-doping process, Fig. 3c,d) after achieving each quasi-equilibrium state 46 in order to probe the physical and/or chemical phenomena at the interface between the BPOE and the electrolyte solution. A frequency range of 10 mHz-10 kHz with an amplitude of 10 mV was applied in all EIS measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The boundary-less mechanism facilitated capacities of greater than 160 mA h g -1 at rates as high as 10 C, far exceeding those of bulk and larger sized (43 nm) particles [275]. Such size-effects could therefore account for the enhanced rate capability displayed by small diameter LiMn2O4 nanorods [270][271][272], and nanowires [265][266][267], which possess both high power and enhanced cycling ability.…”
Section: Limnxoymentioning
confidence: 99%
“…Coupled with relatively low production costs and appreciable electrochemical performance at high discharge rates and elevated temperatures, LiMn2O4 is touted as a potential driver of future EV/HEV battery packs, notably against favourable LiFePO4 candidates [264]. Recent nanostructured morphologies of note include nanowires [265][266][267], nanorods [268][269][270][271][272], nanotubes [273], nanoparticles [269,[274][275][276] and ordered meso/porous electrodes [277,278]. Okubo et al [275] have demonstrated an important size-effect occurring in LiMn2O4 particles, confirming that bulk particle sizes are unable to achieve complete lithiation (up to Li2Mn2O4), due to their lower surface area.…”
Section: Limnxoymentioning
confidence: 99%
“…Layered NCM was first prepared by a solid state reaction at 1000°C in air in 2001 [8]. NCM shows a rechargeable capacity of 150 mAh/g in 3.5-4.2 V or 200 mAh/g in 3.5-5.0 V. Research shows that the NCM has the α-NaFeO 2 structure, which is the characteristic of the layered LiCoO 2 and LiNiO 2 structures and shows larger capacity of more than 150 mAh/g in the voltage range of 2.5-4.2 V with excellent cycle ability and no transformation to spinel phase during electrochemical cycling [9][10][11]. The DSC measurements shows the thermal behavior of NCM is milder than that of LiCoO 2 or LiNiO 2 [12].…”
Section: Structural Characteristics and Mechanism Of Charging And Dismentioning
confidence: 99%